Cleopatra : a novel - El-Arifi, Saara (Ballantine Books, 2026)
"Cleopatra tells her own story in this evocative and sensuous historical epic from the bestselling and award-winning author of Faebound and The Final Strife. You know my name, but you do not know me. Your historians call me seductress, but I was ever in love's thrall. Your playwrights speak of witchcraft, but my talents came from the gods themselves. Your poets sing of my bloodlust, but I was always protecting my children. How wilfully they refuse to concede that a woman could be powerful, strategic, and divinely blessed to rule. Death will silence me no longer. This is not the story of how I died. But how I lived." --